Cueto, M. (2020). El regreso de las epidemias. Salud y sociedad en el Perú del siglo XX. (2. da ed.). Lima. Instituto de Estudios Peruanos. - Gianella Malca, Camila (2021)
Reseña del libro El regreso de las epidemias. Salud y sociedad en el Perú del siglo XX